Executive Committee Minutes 2012-11-01 - Academic Senate:::::::::
Agenda approved. Minutes postponed. Chair Report. Questions for the Provost. Vice Chair Report. Online Instruction Policy approved for Senate agenda. Vice President of Administration and Finance Report. EPC discussion of experimental course and program proposals. Chief Student Affairs Officer Report. EPC Report. FSAC Report. CFA Report. Associated Students Report. Senate agenda approved.